Transformasi Masyarakat Desa: Pengembangan Pemasaran dan Kemitraan - Arif, Muh; Alam, Syamsul; Kalsum, Ummu; Sharon, St. Salmah (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2025)
Purpose – Community service on economic empowerment through entrepreneurship development and skills in Padanglampe' Village, Pangkep Regency, aims to improve the welfare and empowerment of the local community. Design/methodology/approach – This service utilizes a participatory and qualitative approach to identify the needs and economic potential of the community, as well as to develop entrepreneurship training and mentoring programs. Throughout the implementation of this service, a series of training and workshops were conducted, focusing on entrepreneurial skill development and business management. Additionally, direct mentoring and guidance were provided to local business groups to assist them in implementing the knowledge and skills they have acquired. The community service program has successfully fostered collaboration and social networks among local entrepreneurs, increasing community involvement in developing the local economy sustainably. Findings – As a result of this service, there has been a development of local businesses and a reduction in the unemployment rate in Padanglampe' Village, where the community actively engages in entrepreneurship by managing the existing potentials in the village. Originality/value –The benefits of this service include collaboration among local business actors, creating a conducive environment for local economic growth and village community income